Managing students’ academic failure among secondary school students for high productivity in Obingwa LGA of Abia State - Uwaezuoke, Martha-Rose Ifeoma; Oparaji, Israel Chijiuka (S&Co Publishing, 2023)
The study investigated the management of students’ academic failure among secondary school students for high productivity in Obingwa Local Government Area of Abia State. The study was guided by two research questions and two hypotheses. Descriptive survey research design was used while the population of the study comprised thirty public secondary schools. A sample size of 10 secondary schools was selected from the 30 public secondary schools using stratified random sampling technique. Self-designed instrument entitled “Management Students’ Academic Failure Questionnaire” (MSAFQ) was utilized. The validity of the instrument was ensured. Test retest method was used and reliability co-efficient of 0.80 and 0.83 was obtained through Cronbach Alpha Statistics. Mean was used to answer the research questions while Z-test statistics was used to test the hypotheses at 0.05 level of significant. The findings include but not limited to: lack of instructional material and inability of the teachers to stimulate students are causes of academic failures among students. It is therefore recommended that the government or appropriate agency should ensure adequate supply of functional instructional resources and teachers’ should do well to motivate students to learn thereby save students from incessant failures that could mar their future and life expectations.